Cover Picture: Bis(tert‐butylpyrene) Nanotweezers and Nanocalipers: Enhanced Extraction and Recognition Abilities for Single‐Walled Carbon Nanotubes (Chem. Eur. J. 48/2013). Issue 48 (25th November 2013) - Liu, Gang; Rahman, A. F. M. Mustafizur; Chaunchaiyakul, Songpol; Kimura, Takahide; Kuwahara, Yuji; Komatsu, Naoki
<x xml:space="preserve">Abstract</x> Sorting single‐walled carbon nanotubes (SWNTs) attracts great attention in view of their applications. Recently, it was demonstrated that metallic SWNTs with diameters of 0.9–1.0 nm are highly enriched through molecular recognition. In their Full Paper on page 16221 ff., N. Komatsu et al. show that the host molecule, named "nanocalipers", discriminates metallicity and diameter of SWNTs simultaneously to enrich limited kinds of metallic SWNTs. tert‐Butyl substituents at pyrene moieties are found to enhance extraction and recognition abilities of the nanocalipers to SWNTs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>